The effect of mindfulness-based cognitive psychotherapy on quality of life in infertile women - Tahere Rahmani Fard; Seyed Mohammad Kalantarkousheh; Mahbobeh Faramarzi (Tehran University of Medical Sciences, 2017)
Background & Aim: Infertile women experience greater stress in their life and have lower quality of life compared to fertile women. The present study aimed to evaluate the effect of mindfulness-based cognitive psychotherapy (MBCT) on quality of life in infertile women. Methods & Materials: In a randomized clinical trial (IRCT2017021132321N2) with the Solomon four-group design, 60 infertile women referred to Fatemeh Zahra Infertility Research Center in Babol in 2015, were randomly assigned into four groups (15 in the group of experiment with pretest, 15 in the group of experiment without pretest, 15 in the group of control with pretest, 15 in the group of control without pretest). A total of thirty participants in the experimental group received MBCT in eight group sessions (120 minutes, once a week). The control group received no intervention. Thirty participants at the beginning and sixty participants at the end of study completed the Quality of Life Questionnaire (WHOQOL-26). Data were analyzed by the SPSS software version 20 using univariate ANCOVA. Results: The mindfulness-based cognitive psychotherapy improved the quality of life in both experimental groups. The mean scores for all the four domains of quality of life including, physical health, psychological health, social relationships, and environment significantly increased in both experimental groups compared to control groups (P<0.05). Conclusion: The use of MBCT as a reliable method for promoting the quality of life of infertile women is recommended in infertility clinics.